Human Resource Management Processes for Achieving Quality Teachers Through the Lens of Career Progression - Torquido, Sheila Mae; Boquia, Arbaya (Journal of Interdisciplinary Perspectives, 2024)
This study investigates the relationship between human resource management processes and career progression among teachers in DepEd Region XII. Specifically, it examines how selecting and staffing, training and development, compensation and benefits, and employee assistance influence career goals, career navigation skills, and career success measures. Descriptive-predictive correlation analysis was employed using survey data from teachers in four divisions. Findings reveal a significant positive correlation between human resource management processes and career progression, suggesting that effective HR practices can enhance teacher development and career satisfaction. The study's results provide valuable insights for DepEd to improve its HR programs and foster a more supportive environment for teacher growth.